An Architecture for Supporting RFID-Enhanced Interactions in Digital Libraries - Jen Pearson (Research and Advanced Technology for Digital Libraries, 2010)
In this paper, we report the design of an RFID sensing infrastructure for digital libraries. In addition to the architecture of the system, we report its deployment in three different applications to illustrate its use and integration with not only the core DL software, but also web browsers and software for reading documents (e.g. in PDF format). Through this, we demonstrate the utility of RFID support across the entire information seeking cycle.